Conservative strategy in patients with non-ST-segment elevation acute coronary syndromes - Zalewski, Jarosław; Nycz, Krzysztof; Przewłocki, Tadeusz; Andres, Marek; Durak, Monika; Lech, Piotr; Pieniążek, Piotr; Żmudka, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background : Clinical outcomes of patients with non-ST-segment elevation acute coronary syndrome (NSTACS) disqualified from an invasive strategy (InvS) remain incompletely understood. Aim : To investigate short-term results of a conservative strategy (ConS) in a real-life population of patients with NSTACS. Material and methods : 526 patients with NSTACS were retrospectively analysed. Of these, 335 (63.7%) patients were initially qualified for the ConS. In the remaining 191 (36.3%) patients an InvS was applied. Results : The most frequent reasons for disqualification from an InvS in NSTACS patients were TIMI risk score  4 (88.0%), lack of patient consent (3.9%) and pulmonary oedema (3.0%). In the group of InvS, cardiogenic shock on admission was found in 11 (5.8%) patients. In patients who underwent ConS and InvS 30-day mortality rate was 6.0 and 10.5% (p = 0.061), respectively, whereas 30-day mortality in non-shock patients assigned to InvS was 7.9% (p = 0.40 vs. ConS). During primary hospitalization, 27 (8.1%) patients with ConS and 7 (3.7%) with InvS developed symptoms of heart failure (Killip 2-4) (p = 0.049). In the group of InvS, cardiogenic shock on admission (OR 49.5, 95% CI 125-234.2, p < 0.0001) and in patients treated conservatively heart failure during hospitalization (OR 27.4, 95% CI 4.8-155.2, p = 0.003) were independent predictors of 30-day mortality (c-statistics 0.70). Conclusions : In NSTACS patients, low risk of complications at baseline was the main reason for disqualification from InvS. The mortality rate within 30 days did not differ significantly between the two therapeutic groups. Symptoms of heart failure during hospitalization were an independent predictor of death within 30 days in NSTACS patients disqualified from InvS.